Compañeras de allende las fronteras. Estereotipos de género y nación entre las mandos fascistas de España y Alemania - Toni Morant i Ariño (Amnis)
Between 1936 and 1945, the female leaders of Spanish fascism and German Nazism maintained fluid contacts. Born out of an ideological affinity and the awareness of sharing the same political culture, they took the form of numerous study visits and collaboration in a joint project with fascist youth organisations to outline the future of « New Europe ». The existing documentation provides a lot of information on the content of these close relations, but it also contains a great deal of information on the way in which Spanish and German women viewed each other and their respective countries. The text focuses on these views, in a context and with protagonists that hitherto have not been taken into account in studies on gender and nation stereotypes.